One-Pot Synthesis of Aminated Bimodal Mesoporous Silica Nanoparticles as Silver-Embedded Antibacterial Nanocarriers and CO2 Capture Sorbents - Yun Li; Amit Kumar Tiwari; Jingyi Sandy Ng; Geok Leng Seah; Hong Kit Lim; Teeraporn Suteewong; Chor Yong Tay; Yeng Ming Lam; Kwan W. Tan (My University, 2022)
Mesoporous silica nanoparticles have highly versatile structural properties that are suitable for a plethora of applications including catalysis, separation, and nanotherapeutics. We report a one-pot synthesis strategy that generates bimodal mesoporous silica nanoparticles via coassembly of a structure-directing Gemini surfactant (C16-3-16) with a tetraethoxysilane/(3-aminopropyl)triethoxysilane-derived sol additive. Synthesis temperature enables control of the nanoparticle shape, structure, and mesopore architecture. Variations of the aminosilane/alkylsilane molar ratio further enable programmable adjustments of hollow to core-shell and dense nanoparticle morphologies, bimodal pore sizes, and surface chemistries. The resulting Gemini-directed aminated mesoporous silica nanoparticles have excellent carbon dioxide adsorption capacities and antimicrobial properties against Escherichia coli. Our results provide an enhanced understanding of the structure formation of multiscale mesoporous inorganic materials that are desirable for numerous applications such as carbon sequestration, water remediation, and biomedical-related applications.
Keywords: Triethoxysilane; Nanocarriers; Mesoporous organosilica; Mesoporous Materials and Catalysis